Effects of instrument-assisted manipulation and mobilization with movement in chronic non-specific low back pain: A randomized controlled trial - Erol, Erkan; Burak, Mustafa; Elbasan, Bulent (Sage Publications Inc, 2025)
Background Low back pain is the third most reported complaint after headache and chronic fatigue, and more than 80% of the population will experience low back pain at some point in their lives. Object & imath;ve We conducted this study to investigate the effects of instrument-assisted manipulation (IAM) and mobilization with movement (MWM) on joint range of motion (ROM), pain, proprioception, endurance, back awareness, and disability in individuals with chronic nonspecific low back pain (CNSLBP). Methods 51 participants with CNSLBP were randomized to one of three groups: (1) MWM; (2) IAM; or (3) core exercise. Joint ROM, pain, proprioception, endurance, back awareness, and disability were assessed at baseline, week 2 and 6. Results Joint ROM and activity pain scores increased in all groups (p < 0.05). Both activity and resting pain improved in the MWM group (p < 0.001; p = 0.004). Most measures related to proprioception improved in the MWM group (p = 0.005; p = 0.016; p = 0.016). Endurance increased in all groups, but the flexor endurance increase was higher in the MWM group (p < 0.05). Back awareness and disability increased in all groups (p < 0.05), but disability increased most in MWM group (p = 0.022). Conclus & imath;ons MWM could effectively improve pain, proprioception, endurance, and disability.
Keywords: musculoskeletal pain; manual therapy; exercise